Universal Teacher-Child Interaction Training in Early Special Education: A Pilot Cluster-Randomized Control Trial. Issue 2 (March 2021) - Davidson, Bridget C.; Davis, Eileen; Cadenas, Heleny; Barnett, Miya; Sanchez, B. Erika Luis; Gonzalez, Juan Carlos; Jent, Jason
Abstract: Using a pilot matched-pairs cluster-randomized control trial, we evaluated the acceptability and preliminary outcomes of universal Teacher-Child Interaction Training (TCIT-U) with students with disabilities in early special education programs. Twelve classrooms (clusters) were paired by age and type and then randomly assigned within pairs to either TCIT-U (81 students, 20 teachers) or wait-list control (63 students, 16 teachers) with services as usual. We analyzed the effects of TCIT-U on (a) teachers' skills acquisition via masked observational coding and (b) students' behavior and developmental functioning via teacher questionnaires. For child-directed interaction skills, teachers receiving TCIT-U exhibited significantly greater increases in behavior descriptions and labeled praise than teachers who did not receive TCIT-U at posttreatment and follow-up. No significant group differences were observed in use of teacher-directed interaction skills. Qualitative data from teachers expanded on these findings, suggesting that teachers found child-directed interaction skills more acceptable than teacher-directed interaction skills. Teachers receiving TCIT-U reported small but significant improvements in student behavior problems and socioemotional functioning at posttreatment and follow-up, as compared to wait-list students. We discuss considerations for future implementation and tailoring of TCIT for young students with disabilities, which may have positive impacts on future cohorts of students beyond teachers' initial training. Highlights: Evaluation of Teacher-Child Interaction Training in early special education Classrooms were randomly assigned to an intervention or wait-list control group Intervention led to significant increases in positive teacher attention to students No significant intervention effects on teacher-directed interaction skills Intervention led to improved student behavior and socioemotional functioning